Lung function outcomes of cystic fibrosis patients after early-life pulmonary exacerbations: National registry analysis - Ozkan Tabakci, Sati; Uytun, Salih; Eryilmaz Polat, Sanem; Cinel, Guzin; Yalcin, Ebru; Kiper, Nural; Dogru Ersoz, Deniz (Wiley, 2026)
Background Pulmonary exacerbations (PEs) are associated with a subsequent decline in lung function. We aim to evaluate lung function in cystic fibrosis (CF) patients with frequent PEs in their first 2 years of age using spirometry at age 6. Methods This retrospective cohort study included CF patients who were 6 years old from the CF registry of Turkey in 2019. According to the number of PEs, patients were classified: those who had two or fewer PEs in the first 2 years of age were defined as Group 1 and those who had more than two PEs were defined as Group 2. The patients' demographics and clinical characteristics were compared between Group 1 and Group 2. Results The study included 88 patients who had data on PE from their first 2 years and completed their sixth year by 2019. Fifty-nine patients were included in Group 1 and 29 in Group 2. The mean percent-predictive FEV1 (ppFEV1), percent-predictive FVC (ppFVC) values, and the mean age at first PE were lower in Group 2 than in Group 1 (p = 0.019, p = 0.017, p < 0.001). The patients with chronic Pseudomonas aeruginosa (PA) colonization had lower mean ppFEV1 and ppFVC values than those without (p = 0.001, p = 0.001). Patients with PA in respiratory-sample culture during their first PE had lower ppFEV1 and ppFVC values than those with SA (p = 0.046; 0.018). Conclusions This study showed that more frequent PEs in the first 2 years of age and chronic PA colonization were associated with poorer FEV1, FVC, and BMI values in CF patients.
Keywords: chronic colonization; cystic fibrosis; pulmonary exacerbation; respiratory function